PENYELESAIAN KASUS PENAHANAN IJAZAH KARYAWAN KONTRAK ( STUDI KASUS : PUTUSAN NO.145/Pdt.Sus- PHI/2023/PN.Jkt.Pst ): Settlement Of Cases Of Contract Employee Certificates Withholding (Case Study : Decision No.145/Pdt.Sus-Phi/2023/Pn.Jkt.Pst) - Pratiwi, Asturia Dyan (Fakultas Hukum, Universitas Trisakti, 2025)
This writing is done because there are often disputes regarding work agreements with clauses that force the diplomas of workers to be confiscated during the contract. The problem formulation is how to resolve industrial relations disputes based on Law No. 2 of 2004 concerning the resolution of industrial relations disputes. The type of research uses descriptive normative legal research. Secondary data is analyzed qualitatively. Concluding uses deductive logic. The study results indicate no regulations regarding the validity or otherwise of an employer withholding a worker's original diploma. A work agreement containing requirements regarding the retention of the worker's original diploma is permitted based on an agreement between the two parties referring to subjective conditions related to the agreement's validity, as stated in Article 1320 of the Civil Code. The existence of a diploma retention clause in a work agreement is a violation and is an unlawful act.